“PENGARUH PERCEIVED VALUE TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI OLEH KEPUASAN KONSUMEN (STUDI PADA MIE AYAM BANG UCUP PONOROGO) - Dina Puspitasari; Hadi Sumarsono; Sri Hartono (Jurnal AKTUAL, 2022)
This study aims to determine the direct effect of Perceived Value on Consumer Loyalty and Satisfaction, the effect of Satisfaction on Consumer Loyalty and whether Satisfaction mediates the effect of Perceived Value on Consumer Loyalty in Bang Ucup Ponorogo Chicken Noodles. This study uses a quantitative method of path analysis. There are 45 respondents. sampling using purposive sampling technique with a questionnaire as a data collection tool. From the results of data analysis, it is found that Perceived Value has an effect on Consumer Loyalty and Satisfaction. Satisfaction has an effect on Consumer Loyalty and mediates Perceived Value on Consumer Loyalty in Mie Ayam Bang Ucup Ponorogo. “